Adaptation of Tinnitus Retraining Therapy (TRT) in the Brazilian population - Ganz Sánchez, Tanit; dos Santos Ferrari, Gisele Munhóes (Auditio, 2021)
TRT is being widely established in different centers and providing the best results in the relief of patients with tinnitus. In Brazil, two facts contribute to a "resistance" to this method: the delay in the beginning to perceive the "long-awaited" improvement and the lack of knowledge about TRT. Our objective is to describe the experience with TRT in Brazil, showing some adaptations of the official method. We reviewed 161 files of tinnitus patients who have started TRT. The analysis of the results was carried out 12 months after the indication of TRT, separating the patients into 3 groups according to the category and mode of treatment: a) categories 1, 3 and 4 treated with ’more advice sessions’. broadband noise generators’ (n = 38): tinnitus has improved in 73.3%; b) categories 1, 3 and 4 that have rejected the noise generators and have received ’advice sessions plus soft ambient sounds’ (n = 74): tinnitus has improved by 80%; c) category 2 treated with ’advice sessions, hearing aids and soft ambient sounds’ (n = 49): only 23 agreed to wear hearing aids, however 16 of them automatically presented tinnitus masking and were excluded from the result of TRT. In this study, patients have shown great restriction in wearing headphones or noise generators, so the principles of TRT had to be reinforced through the use of soft ambient sounds. Those who have followed the TRT protocol have shown excellent tinnitus improvement rates.